Penjadwalan dan Penentuan Rute Distribusi Komoditas ke Wilayah Timur Indonesia - Erika Fatma; Winanda Kartika (Jurnal Optimasi Sistem Industri, 2017)
Indonesia’s geographical conditions, particularly in the eastern region, which is archipelago has its own challenges in the distribution of commodities, such as rice. Most of the rice needed in eastern Indonesia, is still supplied from Java Island. The most suitable transportation mode for rice distribution in the eastern region of Indonesia, is by sea (ships). In this study, a ship routing and scheduling model for commodity distribution in the eastern region of Indonesia was developed, using capacitated vehicle routing problem (CVRP) method. The model was built by considering the number of demands on the destination, ship capacity, and ports service time. Modeling was developed to determine distribution route and schedule that can provide total minimum cost and meet all of the restrictions.